The Influence of Information Technology-Based Banking Services Against Customer Satisfaction - Elli Sulistyaningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Increasingly advanced technology in the world of banking transactions began to use computer-based technology to facilitate transactions with customers. who used to serve customers by having to meet / customers come to bank branches provided by the bank where he used to save / invest it has become easier because banks have started using computer-based technology and now they can access via the internet even with mobile